Endocrine signals fine-tune daily activity patterns in Drosophila. - Pauls, D.; Selcho, M.; Räderscheidt, J.; Amatobi, K.M.; Fekete, A.; Krischke, M.; Hermann-Luibl, C.; Ozbek-Unal, A.G.; Ehmann, N.; Itskov, P.M.; Kittel, R.J.; Helfrich-Förster, C.; et al. (Current Biology, 2021)
Animals need to balance competitive behaviors to maintain internal homeostasis. The underlying mechanisms are complex but typically involve neuroendocrine signaling. Using Drosophila, we systematically manipulated signaling between energy-mobilizing endocrine cells producing adipokinetic hormone (AKH), octopaminergic neurons, and the energy-storing fat body to assess whether this neuroendocrine axis involved in starvation-induced hyperactivity also balances activity levels under ad libitum access to food. Our results suggest that AKH signals via two divergent pathways that are mutually competitive in terms of activity and rest. AKH increases activity via the octopaminergic system during the day, while it prevents high activity levels during the night by signaling to the fat body. This regulation involves feedback signaling from octopaminergic neurons to AKH-producing cells (APCs). APCs are known to integrate a multitude of metabolic and endocrine signals. Our results add a new facet to the versatile regulatory functions of APCs by showing that their output contributes to shape the daily activity pattern under ad libitum access to food.